2016
DOI: 10.3126/jcmsn.v11i4.14320
|View full text |Cite
|
Sign up to set email alerts
|

Non degenerative disease in MRI cervical spine of symptomatic patients

Abstract: Background & Objectives: The most common etiology of neck pain is degenerative disc disease, however non-degenerative disease can be important cause of neck pain. This study aims to study the non-degenerative findings in cervical MRI in symptomatic patients with neck and radicular pain.Materials & Methods: The study was a institutional record based retrospective study performed for the duration of 3 years. MRI performed for patients with neck pain and/ or radiculopathy were reviewed. Patients with post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 6 publications
2
15
2
Order By: Relevance
“…Cases of spinal injuries occurring during the road accidents are frequently reported in the literature, and from 30% to 75% of these cases are related to the cervical injures [ 27 35 ]. Some researches have shown that during traumatic and nontraumatic accidents the fractures or dislocation of vertebrae or damage of soft tissue including the spinal cord was usually found at C4–C8 level [ 28 , 29 , 31 , 33 , 36 , 37 ] and low intervertebral disc levels were more exposed to damage because of their size [ 38 ]. Earliest studies have shown that there was a wide age range of patients with various kinds of cervical injures, but the largest numbers of cases were between 31 and 59 years [ 27 , 28 , 31 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cases of spinal injuries occurring during the road accidents are frequently reported in the literature, and from 30% to 75% of these cases are related to the cervical injures [ 27 35 ]. Some researches have shown that during traumatic and nontraumatic accidents the fractures or dislocation of vertebrae or damage of soft tissue including the spinal cord was usually found at C4–C8 level [ 28 , 29 , 31 , 33 , 36 , 37 ] and low intervertebral disc levels were more exposed to damage because of their size [ 38 ]. Earliest studies have shown that there was a wide age range of patients with various kinds of cervical injures, but the largest numbers of cases were between 31 and 59 years [ 27 , 28 , 31 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some researches have shown that during traumatic and nontraumatic accidents the fractures or dislocation of vertebrae or damage of soft tissue including the spinal cord was usually found at C4–C8 level [ 28 , 29 , 31 , 33 , 36 , 37 ] and low intervertebral disc levels were more exposed to damage because of their size [ 38 ]. Earliest studies have shown that there was a wide age range of patients with various kinds of cervical injures, but the largest numbers of cases were between 31 and 59 years [ 27 , 28 , 31 , 33 , 34 ]. Moreover, reported cervical injury cases related mainly to man rather than woman [ 27 , 31 , 32 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,[41][42][43][44][45][46][47][48] These phenotypes have since been heavily associated with concomitant symptomatology and are thought to contribute to axial neck and/or back pain, worse surgical outcomes, and decreased health-related quality of life scores. 44,[49][50][51][52][53] Notably, MRI has allowed for particularly detailed characterization of intervertebral discs and endplates, leading to the development of validated classification schemes as proposed by Pfirrmann and Modic. Pfirrmann grade is obtained by evaluating the intensity of intervertebral discs on T2-weighted images and is a reliable five-tiered classification scheme for characterization of disk degeneration.…”
Section: Mrimentioning
confidence: 99%
“…[60][61][62][63][64] This, combined with associations with pain and disability, has demonstrated that MRI is not only a convenience but a necessity in the delivery of standard of care. 44,[49][50][51][52][53] Despite these strengths, traditional T1-and T2-weighted MRI has notable limitations.…”
Section: Mrimentioning
confidence: 99%